2022
DOI: 10.1002/pc.27108
|View full text |Cite
|
Sign up to set email alerts
|

Thermal characterization of epoxy bilayer hybrid composites reinforced with kenaf and oil palm fibers

Abstract: Natural fiber-based materials are widely accepted in the composite sector as a substitute for synthetic fiber, particularly in structural and semi-structural implementations in the automotive and aerospace industries, reflecting a recent trend and increased awareness of the importance of sustainable product design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Considering that the glass transition temperature of the epoxy matrix in CFRP laminates used in this study was about 120 C and the thermo-oxidative decomposition temperature was 183 C, the high temperature generated by the energy accumulation effect on the surface of CFRP specimens after a long-term plasma treatment might affect the surface properties of composites, [22,23] which thereafter would affect the bonding properties of the CFRP bonded components.…”
Section: Temperature Field Distribution On the Surface Of Cfrp Specimenmentioning
confidence: 99%
“…Considering that the glass transition temperature of the epoxy matrix in CFRP laminates used in this study was about 120 C and the thermo-oxidative decomposition temperature was 183 C, the high temperature generated by the energy accumulation effect on the surface of CFRP specimens after a long-term plasma treatment might affect the surface properties of composites, [22,23] which thereafter would affect the bonding properties of the CFRP bonded components.…”
Section: Temperature Field Distribution On the Surface Of Cfrp Specimenmentioning
confidence: 99%
“…Fiber addition more than the optimum range will inversely affect the mechanical and wear properties of epoxy-based composites (Singha and Thakur 2008;Nirmal et al 2012;Shuhimi et al 2016;Kumar et al 2019). It was also observed that lignocellulosic fiber has its better application by adding the fibers in equal weight percentages (Satheesh Kumar et al 2010;Liu et al 2019;Nanda and Satapathy 2021;Hanan et al 2023). The areca natural fibers up to 20 wt% observed better mechanical properties with epoxy-based composites (Johnson 2019).…”
Section: Introductionmentioning
confidence: 96%
“…The objective of this study was to provide valuable insights on the effectiveness and compatibility of various resin-fiber combinations in the production of composite tubes (Supian et al 2018;Hanan et al 2022;Palanisamy et al 2023b). Eyer et al (2016), studied compression tests and found that the failure mode of specimens can be influenced by factors such as slenderness.…”
Section: Introductionmentioning
confidence: 99%